Characterization and low-cost preservation of Chromobacterium violaceum strain TRFM-24 isolated from Tripura state, India - Sushil K. Sharma; Rakhi Dhyani; Ees Ahmad; Pankaj K. Maurya; Madhu Yadav; Ramesh Chandra Yadav; Vinod Kumar Yadav; Pawan K. Sharma; Mahaveer P. Sharma; Aketi Ramesh; Anil K. Saxena (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background Chromobacterium species, through their bioactive molecules, help in combating biotic and abiotic stresses in plants and humans. The present study was aimed to identify, characterize and preserve in natural gums the violet-pigmented bacterial isolate TRFM-24 recovered from the rhizosphere soil of rice collected from Tripura state. Results Based on morphological, biochemical and 16S rRNA gene sequencing, the isolate TFRM-24 was identified as Chromobacterium violaceum (NAIMCC-B-02276; MCC 4212). The bacterium is saprophytic, free living and Gram negative. The strain was found positive for production of IAA, cellulase, xylanase and protease, and showed tolerance to salt (2.5%) and drought (-1.2 MPa). However, it showed poor biocontrol activity against soil-borne phytopathogens and nutrient-solubilizing abilitiets. C. violaceum strain TRFM-24 did not survive on tryptic soya agar (TSA) beyond 12 days between 4 and 32 °C temperature hence a method of preservation of this bacterium was attempted using different natural gums namely Acacia nilotica (babul), Anogeissus latifolia (dhavda), Boswellia serrata (salai) and Butea monosperma (palash) under different temperature regime (6–32 °C). The bacterium survived in babul gum (gum acacia), dhavda and salai solution at room temperature beyond a year. Conclusion Based on polyphasic approach, a violet-pigmented isolate TRFM-24 was identified as Chromobacterim violaceum which possessed some attributes of plant and human importance. Further, a simple and low-cost preservation method of strain TRFM-24 at room temperature was developed using natural gums such as babul, dhavda and salai gums which may be the first report to our knowledge.